2000
DOI: 10.2144/00294rr01
|View full text |Cite
|
Sign up to set email alerts
|

PCR Amplification on a Microarray of Gel-Immobilized Oligonucleotides: Detection of Bacterial Toxin- and Drug-Resistant Genes and Their Mutations

Abstract: PCR amplification on a microarray of gel-immobilized primers (microchip) has been developed. One of a pair of PCR primers was immobilized inside a separate microchip polyacrylamide porous gel pad of 0.1 x 0.1 x 0.02 (or 0.04) micron in size and 0.2 (or 0.4) nL in volume. The amplification was carried out simultaneously both in solution covering the microchip array and inside gel pads. Each gel pad contained the immobilized forward primers, while the fluorescently labeled reverse primers, as well as all compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…Oligonucleotide based DNA arrays have been used for parallel species identification and rifampin resistancerelated mutations in mycobacteria (Troesch et al, 1999) and, more specifically, for the detection of M. tuberculosis strains that are resistant to rifampin (Yue et al, 2004) or isoniazid, kanamycin, streptomycin, pyrazinamide, and ethambutol (Gegia et al, 2008). Oligonucleotide microarrays were developed to analyze and identify drugresistant M. tuberculosis strains, and it was found that the results were comparable with those of standard antimicrobial susceptibility testing (Strizhkov et al, 2000;Mikhailovich et al, 2001). A low-cost and -density DNA microarray was designed to detect mutations that confer isoniazid and rifampin resistance in M. tuberculosis isolates.…”
Section: Gene Expression Profiles Of Drugs Resistance Inhibitors Anmentioning
confidence: 99%
“…Oligonucleotide based DNA arrays have been used for parallel species identification and rifampin resistancerelated mutations in mycobacteria (Troesch et al, 1999) and, more specifically, for the detection of M. tuberculosis strains that are resistant to rifampin (Yue et al, 2004) or isoniazid, kanamycin, streptomycin, pyrazinamide, and ethambutol (Gegia et al, 2008). Oligonucleotide microarrays were developed to analyze and identify drugresistant M. tuberculosis strains, and it was found that the results were comparable with those of standard antimicrobial susceptibility testing (Strizhkov et al, 2000;Mikhailovich et al, 2001). A low-cost and -density DNA microarray was designed to detect mutations that confer isoniazid and rifampin resistance in M. tuberculosis isolates.…”
Section: Gene Expression Profiles Of Drugs Resistance Inhibitors Anmentioning
confidence: 99%
“…For real-time measurements of SYBR ® green I fluorescence, the experimental setup that was described earlier consisted of fluorescent microscope equipped with thermotable, a charge coupled device camera, a temperature controller, 13,19,20 and specialized software IMAGEEXPRESS ® ͑Biochip-EIMB, Russia͒. Images were acquired every cycle at the end of elongation step.…”
Section: E Data Acquisition and Image Processingmentioning
confidence: 99%
“…12 An independent cohort of researchers has been working on implementation of SP-PCR to amplification of specific targets on microarray. The suitability of microarray-based SP-PCR for detection of mutations and polymorphisms, [13][14][15][16] detection of toxin genes and microorganisms, 13,[17][18][19][20] eukaryotic expression profiling, 20 methylation analysis, 21 and generation a͒ of extremely long microarray probes 22 has been successfully demonstrated. Some of these works utilized the traditional immobilization of solid phase primers on a functionalized glass surface, while the others used a polyacrylamide gel as a support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain such information, we analyzed HIV-1 genetic variants, along with conventional sequencing, by using oligonucleotide microarrays that have already been proven to be used as a diagnostic tool for identifying nucleic acid polymorphisms (24,29,41).…”
mentioning
confidence: 99%